HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP BIDAN TENTANG INISIASI MENYUSUI DINI (IMD) TERHADAP PERILAKU BIDAN MELAKUKAN INISIASI MENYUSUI DINI (IMD) - Triana, Erika; ., Sumarni; Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2010)
Asuhan Persalinan Normal (APN) always develops time by time. APN have slightly changed in its detail explanation about early breast feeding initiation that has many benefit, but not all of midwifes do it. Midwife’s lack of early breast feeding initiation information and knowledge is causal factor for them who do not practice early breast feeding initiation for themselves. To obtain the correlation between midwife’s knowledge and behavior of early breast feeding initiation toward midwife’s early breast feeding initiation practice. The study is observational research by crossectional approach. The population of the research is 36 midwifes who have Bidan Praktek Swasta (BPS) in Purwokerto. Total sampling is used in this research by observing all the population as the sample. Actually, there are only 30 midwifes who have the willing to be respondents. The research use chi-square as the analysis method. Respondents with adequate knowledge category of early breast feeding initiation is 16 midwifes (53,3%) and 18 respondent (60%) agree with early breast feeding initiation as their behavior. There is balance respondent behavior who do early breast feeding initiation and do not practice it as amount 15 respondents (50%). 4) There is significant correlation between the knowledge and respondents’ behavior of early breast feeding initiation (p = 0,000) with contingency coefficient at 0,626 as high level. 5) There is significant correlation between behavior and practice of early breast feeding initiation (p = 0,025) with low contingency coefficient at 0,378. There is correlation between the knowledge about early breast feeding initiation and early breast feeding initiation practice; then there is correlation between the behavior of early breast feeding initiation and early breast feeding initiation practice. It is desirable that public health implementer practicing early breast feeding initiation in every child bearing.   Key words : knowledge level, midwife behavior, early breast feeding initiation practice